Desain Dan Manufaktur Mekanisme Pelubang Tanah Mengggunkan Sistem Tugal Pada Tilling Machine Untuk Pemupukan Kelapa Sawit - Arief, Dodi Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Generally, the agriculturist applying the fertilization method by spread fertilize around the plants. This procedure is efficient enough but its effectiveness is poor. Fertilizer applicationby immersing in palm disc area will increase the efficient and effective uptake of NPK by plants, furthermore increase plants productivity, save the quantity of fertilize application, anddecrease environmental pollution. The purpose of this research is to design and create tugal in masking fertilize palm that capable of rapidly perforation. The method of this research is used to get information about the fertilization technique. After finding the information process, measurement tools that already exist is done, it's used plow or tilling machine, the toolredrawn and tugal revelation which be install on tools. After the drawing had done, do the print out of drawing, furthermore do the manufacturing process. According to the calculated, we get tugal's diameter design was 7,62 cm, length 20 cm, whereas tugal's position within 44,48 cm from central wheel, the maximum safety factor was 15, whereas displacementmaximum 0,02054 mm and displacement minimum 0 mm, the result shows that tugal's system is save to used. Time fertilization system manual unknown 3 hours, 30 minutes perhectar, whereas fertilization with tugal's system was shorter time, that is 1 hours 28 minutes.Keywords: land punch, tugal, fertilization mechanism.